ØªØ±Ø¨ÙŠØ© Ø§Ù„Ø£Ø·ÙØ§Ù„ ÙÙŠ Ù†Ø¸Ø±ÙŠØ© Ø§Ù„Ù…Ø¹Ø±ÙØ© ÙÙŠ Ø§Ù„Ù‚Ø±Ø¢Ù† Ø§Ù„ÙƒØ±ÙŠÙ… - Saefullah, Ujang; Zaidi, Ahmad; Suparman, Dede (Jurnal Pendidikan Islam, 2016)
This study aims to explore the instructions of the Qurâ€™an on epistimologi education of children. Based on the idea that childhood is a phase of life that is very important and influential on subsequent periods. Educational success in childhood will have a positive impact on the personality and life of the child in the future. As well as failure. This study is the library research with a qualitative approach. The primary data sources are the Qurâ€™an and Tafsir. While the secondary data sources are books related to the theme of research. The research results showed that the Qurâ€™an very concerned about the education of children and encourage parents and teachers to carry out such a comprehensive education. According to the Qurâ€™an children can be jewelry of the world (zÃ®nat al-hayÃ¢t al-dunyÃ¢), a gem that boast (qurrata aâ€™yun), trial for parents (fitnah), and enemies ('aduww). Several things related and affect a child's education is the goal, materials, methods and educator. Everything has to be integrated in an integrated manner for all the requirements are met properly. Â